Political skill reduces the negative impact of distrust. Issue 5 (12th September 2016) - Coleman Gallagher, Vickie; Meurs, James A.; Harris, Kenneth J.
Abstract : Purpose: A number of studies have explored the benefits (e.g. enhanced job performance and reduced strain), of being politically skilled. Within the framework of uncertainty management theory, the purpose of this paper is to explore the benefits of high political skill to affective commitment, job satisfaction, and perceived job mobility, under conditions of distrust in management. Design/methodology/approach: Sales representatives were surveyed and moderated multiple regression analyses were conducted to analyze the data. Findings: The authors found that as distrust increased, affective commitment decreased for all persons, but was most pronounced for persons low on political skill. However, distrust in management had no impact on job satisfaction for those high on political skill, allowing persons high on political skill to enjoy their jobs despite high levels of distrust (an intrapsychic benefit of political skill). Finally, as distrust in management increased, persons high on political skill had increased perceived job mobility. Research limitations/implications: This study is cross-sectional, limiting conclusions about causality in the relationships studied and leaving open the possibility of reverse causation. Practical implications: This research has important implications, such that, under conditions of distrust, persons low on political skill are less committed, more dissatisfied, and feel a sense of job immobility, which could lead to poor work outcomes, such as decreased job performance. Originality/value: The study is the first to examine how being politically skilled benefits employee outcomes when the employee distrusts management.